Sexual Street Harassment as a Limit to the Exercise of Female Citizenship: An Analysis from the Perspective of Normative Pluralism and the Need to Promote Differentiated Citizenship Based on the case of Villa El Salvador - Basurto Basurto, Telma Lucia (2023)
Sexual street harassment is one of the most normalized types of gender violence in Peruvian society; however, little has been explored about its impact on the exercise of female citizenship. Using the case study of Villa El Salvador as a starting point, we analyse how this type of violence impacts on the capacity for agency of Salvadoran villa women, taking into account the parameters of Dhal's normative pluralism, which establishes minimum democratic conditions such as the possibility of (i) formulating preferences, (ii) publicly expressing preferences, and (iii) being treated equally in the political system. Finally, when contrasting the parameters established by Dhal with the exercise of citizenship by Salvadoran Villa women, it can be seen that although Salvadoran Villa women recognize the existence of sexual street harassment as a barrier to exercising their citizenship, they understand it as a "necessary evil to be overcome" if political representation in the political system of Villa El Salvador is their objective.